Análise cladística de Toxotarsinae (Diptera, Calliphoridae) - Tauhyl, Luís Gustavo Moreli (Universidade Federal de São Carlos, 2013)
The Family Calliphoridae is a diverse group of taxonomic, biogeographic, veterenary, forensic and medical importance, with more than 1200 species. The subfamily Toxotarsinae is endemic for the Neotropical region, has eleven species and is distributed mainly in the Andes countries and south of Brazil. Several authors have already studied this group and contributed with wide literature. The Toxotarsinae species are easily recognizable, but there are some difficulties to classify higher-specific taxa. This is the first phylogeny made for Toxotarsinae and it was necessary for better understanding of this group evolution. The aim of this work was to study the relationship among Toxotarsinae species through cladistics analysis. The character matrix was developed exclusively with morphological information. It was performed heuristic analisys using pacimony with equal weighting analyses obtained from Winclada and implied weighting obtained with TNT. The ingroup was compound for all Toxotarsinae species, Toxotarsus ambrosianus, T. nigrocyaneus, T. humeralis, S. chlorogaster, S. magellanica, S. dichroa, S. splendida, S. roraima, S. versicolor e S. maurii, and Neta chilensis, and the outgroup was compound by: Lucilia cuprina (Wiedemann, 1830), Calliphora nigribasis (Macquart, 1851) e Chrysomya megacephala (Fabricius, 1775). Equal weighting analysis resulted in only one most parsimoniously topology ((Sarconesia roraima + (Neta chilensis + S. magellanica)) + (S. splendida + (S. maurii + (S. versicolor + (S. dichroa + (S. chlorogaster + (Toxotarsus nygrocianeus + (Toxotarsus humeralis + Toxotarsus ambrosianus)))))))), with L=105, IC=58 e IR=71. Toxotarsinae appears as a monophyletic group, supported by nine synapomorphies. The ingroup species formed two branches: Sarconesia roraima+ supported by two synapomorphies, and S. splendida+ supported by ten synapomorphies. Implied weighting analysis resulted one tree, with different topologies with k values between 1 3. Based on the obtained topologies, the genus Sarconesia is polyphyletic and the other two genera, Neta and Toxotarsus, are among Sarconesia. The original Toxotarsus species remain togheter and supported by eleven synapomorphies at the apex of S. splendida+ clade. The taxa distribution in topology obligates the proposition of nomenclatural changes. Neta chilensis of S. roraima+ branch will be transferred to genus Sarconesia, and S. splendida+ branch will be transferred to Toxotarsus. An identification key was developed with the new combinations is presented.
Cladistic analysis for the Toxotarsinae (Diptera: Calliphoridae)
Keywords: Análise cladística; Sistematics; Mosca-varejeira; Diptero; Sistemática; Taxonomia; Callihoridae; Toxotarsinae; Diptera; Taxonomy; Calliphoridae; Toxotarsinae; CIENCIAS BIOLOGICAS::BIOLOGIA GERAL